Training visual attention improves basketball three-point shot performance under pressure - Moeinirad, S.; Abdoli, B.; Farsi, A.; Ahmadi, N. (Sport Sciences for Health, 2022)
Purpose The present study aimed to investigate the efficacy of a QE-training duration on improving the performance and accuracy of basketball three-point shot and determined whether such training protected against attentional disruptions associated with performing under pressure.